Inquiring Students’ Alternative Conceptions about Floating and Sinking Objects - Bessas, Nikos; Tzanaki, Eleni; Vavougios, Denis; Plagianakos, Vassilis P. (International Journal of Engineering Pedagogy (iJEP), 2024)
The aim of this study is to determine the misconceptions of Greek junior high school students regarding the floating and sinking of a body through the concept of density. Density is included in most international curricula for this age group and is revisited in Greek junior high schools after being introduced in primary school. After interviews with teachers who teach the physics course, in order to discover the students’ way of thinking and their common misconceptions, the researchers of this study created targeted questionnaires for students aged 11–12 years old. During the 2022–23 school year, the questionnaires were handed out to 47 first-grade students at a junior high school in Athens, Greece. Before being administered to the students, the questionnaires were subjected to a content validity test by five physics experts according to Aiken’s V index. Then, they were completed by the students before the lesson was taught. After the students had completed the initial questionnaire, a teaching proposal focused on the density-based approach was presented to them. Subsequently, the students filled out the same questionnaire again following the instructional session. Statistical analysis demonstrated a notable enhancement in the comprehension of the misconceptions addressed in this study, with the rates of improvement varying between 18.08% and 52.13%. Consequently, the instructional proposal proved to be instrumental in advancing students’ conceptual understanding of floating and sinking within the framework of density interpretation.